Terminal osseous dysplasia with pigmentary defects; Case and brief review of filamin A‐related disorders. (9th June 2015) - Bhabha, Friyana K; Walsh, Maie; Orchard, David; Savarirayan, Ravi
Abstract: Terminal osseous dysplasia with pigmentary defects (TOD) is an extremely rare X‐linked dominant disorder, which is characterised by cutaneous digital fibromas, pigmentary skin defects and skeletal abnormalities. A single mutation in the last nucleotide of exon 31 of the filamin A gene ( FLNA ) has recently been identified as a cause of the disease. We describe a case of an 18‐month‐old girl with the clinical phenotype of TOD and the disease‐specific FLNA mutation confirmed by genetic testing. This report highlights the importance of recognising this distinct phenotype that can present to a wide variety of health‐care professionals, and reviews the spectrum of filamin A disorders.